A node localisation approach based on mobile beacon using particle swarm optimisation in wireless sensor networks. (2017) - Zhang, Xihai; Wang, Tianjian; Fang, Junlong
In most applications of wireless sensor network (WSN), the positions of nodes are important for environmental sensing, search and rescue, and geographical routing and tracking, and so on. An accurate and simple scheme of mobile-assisted localisation for the unknown wireless channel loss model is proposed in this paper. One localisation algorithm is implemented using the particle swarm optimisation (PSO). For improving the localisation performance, the path planning method based on a kind of grid scan is suggested. To evaluate the proposed localisation algorithm, the results of localisation algorithm based on multilateration and the iterative multilateration are also provided. Furthermore, the weight factor τ in the constructed fitness function is also discussed. Overall, it is obtained that the localisation effect of the proposed scheme is better than that of the localisation scheme based on the multilateration and the iterative multilateration for the unknown wireless channel loss model by the simulation experiments.